Paraneoplastic limbic encephalitis presenting as a neurological emergency: a case report - Mehta Brijesh P; Xia Zongqi; Ropper Allan H; Kesari Santosh (Journal of Medical Case Reports, 2010)
Abstract Introduction Paraneoplastic limbic encephalitis remains a challenging clinical diagnosis with poor outcome if it is not recognized and treated early in the course of the disease. Case Presentation A 65-year-old Caucasian woman presented with generalized tonic-clonic seizures and increasing confusion shortly after a lung biopsy that led to the diagnosis of small-cell lung cancer. She had a complicated hospital course, and had recurrent respiratory distress due to aspiration pneumonia, and fluctuating mental status and seizures that were refractory to anti-epileptic drug treatment. Routine laboratory testing, magnetic resonance imaging of the brain, electroencephalogram, lumbar puncture, serum and cerebrospinal fluid tests for paraneoplastic antibodies, and chest computed tomography were performed on our patient. The diagnosis was paraneoplastic limbic encephalitis in the setting of small-cell lung cancer with positive N-type voltage-gated calcium channel antibody titer. Anti-epileptic drugs for seizures, chemotherapy for small-cell lung cancer, and intravenous immunoglobulin and steroids for paraneoplastic limbic encephalitis led to a resolution of her seizures and improved her mental status. Conclusion Early recognition of paraneoplastic limbic encephalitis and prompt intervention with immune therapies at the onset of presentation will probably translate into more favorable neurological outcomes.